Factors influencing successful establishment of exotic Pinus radiata seedlings with co-introduced Lactarius deliciosus or local ectomycorrhizal fungal communities - Wang, Ran; Wang, Yanliang; Guerin-Laguette, Alexis; Zhang, Peng; Colinas, Carlos; Yu, Fuqiang (Frontiers in Microbiology, 2022)
An introduction of exotic or non-native trees may fail due to a lack of suitable fungal partners. We planted exotic Pinus radiata in Xifeng, Guizhou Southwest China. Strategies to introduce P. radiata seedlings either colonized with an ectomycorrhizal fungus (EcMF), Lactarius deliciosus, or expect them to form familiar/new associations with local EcMF in a new habitat were studied to know how P. radiata could be successfully established over a period of 2.5 years. Plant height and needle nutrient acquisition, the persistence of the co-introduced L. deliciosus, and fungal community composition in rhizosphere soil and root tips were analyzed. In addition, a greenhouse bioassay experiment of local soil to assess the differences in the EcMF community between exotic and native pine seedlings was also conducted. The current results demonstrated that P. radiata could establish in the Xifeng plantation with or without co-introduced L. deliciosus. The co-introduced L. deliciosus might be naturalized with P. radiata in the new area since it has been fruited for 2 years with high relative abundance in mycorrhizosphere soil. L. deliciosus pre-colonization significantly altered the mycorrhizosphere fungal composition and it had a positive correlation with nitrogen acquisition of P. radiata. Host identity had no effect on fungal composition since exotic P. radiata and native P. massoniana recruited similar local fungal communities in early establishment or in plantation. The cosmopolitan species Suillus placidus, with high relative abundance, formed a familiar association with P. radiata. The greenhouse bioassay experiment further showed that Suillus sp. contributed relatively higher total extracellular enzymes by forming ectomycorrhizas with P. radiata and the same type of ectomycorrhiza of P. radiata and P. massoniana showed different enzymatic functions. Our study indicated that exotic P. radiata could be a suitable tree capable to get established successfully in the Xifeng plantation either by interaction with the co-introduced L. deliciosus or with a local EcMF, but we should be cautious about large-scale planting of P. radiata. L. deliciosus persisted in plantation and more attention should be paid to local EcMF community changes induced by the introduced L. deliciosus.